ClpP-deletion impairs the virulence of Legionella pneumophila and the optimal translocation of effector proteins - Zhao, Bei-bei (BMC Microbiol, 2016)
BACKGROUND: The opportunistic bacterial pathogen Legionella pneumophila uses substrate effectors of Dot/Icm type IVB secretion system (T4BSS) to accomplish survival and replication in amoebae cells and mammalian alveolar macrophages. During the conversion between its highly resistant, infectious dormant form and vigorously growing, uninfectious replicative form, L. pneumophila utilizes a complicated regulatory network in which proteolysis may play a significant role. As a highly conserved core protease, ClpP is involved in various cellular processes as well as virulence in bacteria, and has been proved to be required for the expression of transmission traits and cell division of L. pneumophila. RESULTS: The clpP-deficient L. pneumophila strain failed to replicate and was digested in the first 3 h post-infection in mammalian cells J774A.1. Further investigation demonstrates that the clpP deficient mutant strain was unable to escape the endosome-lysosomal pathway in host cells. We also found that the clpP deficient mutant strain still expresses T4BSS components, induces contact-dependent cytotoxicity and translocate effector proteins RalF and LegK2, indicating that its T4BSS was overall functional. Interestingly, we further found that the translocation of several effector proteins is significantly reduced without ClpP. CONCLUSIONS: The data indicate that ClpP plays an important role in regulating the virulence and effector translocation of Legionella pneumophila. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12866-016-0790-8) contains supplementary material, which is available to authorized users.